Análise de SNPs em genes de pigmentação humana em indivíduos com olhos negros e pele clara - Gubert, Diego Wordell (2015)
The understanding of gene function in the determination of externally visible traits (EVTs) has several uses in human population evolutionary studies and in forensic investigations. With regards to the latter, a fair amount of effort has been made to discover an easy and efficient model for the prediction of eye and skin color in humans. The obvious advantage of the prediction of such EVTs through the use of DNA is that it can be incorporated as routine procedure in forensic labs and be applied to police investigations. In the present study, we combined the genotypes of eight SNPs in pigmentation-related genes, rs4778138 (OCA2; SNP G>A); rs12913832 (HERC2; SNP A>G); rs16891982 (SLC45A2; SNP C>G); rs8045560 (MC1R; SNP C>T); rs1426654 (SLC24A5; SNP G>A); rs2733832 (TYRP1; SNP C>T); rs1042602 (TYR; SNP C>A); rs916977 (HERC2; SNP A>G), with multiple analytical approaches. A total of 116 individuals from a South of Brazil Snow White population (Dark Eye and Light Skin) were analyzed to identify the genotypephenotype relationship of these SNPs according skin or eye color. Previous studies have shown an association of three SNPs with Dark Eye and Skin (DES; from African populations) and five SNPs with Light Eye and Skin (LES; from European populations). Discriminant Function Analysis (DFA) was performed to obtain the distribution of the individuals among the DES and LES clusters. rs4778138 (OCA2), rs12913832 (HERC2), and rs916977 (HERC2) presented an 82% relationship with the DES cluster, indicating an association with the dark eye phenotype and rs16891982 (SLC45A2), rs8045560 (MC1R), rs1426654 (SLC24A5), rs2733832 (TYRP1), and rs1042602 (TYR) presented a 90% relationship with the LES cluster, indicating an association with light skin phenotype.